Análise privada e social de um abatedouro de galinha caipira no município de Horizonte - CE - Lima, Raquel Alexandre (2020)
Brazilian family farming has gained great prominence in recent years for making several products available for consumption and the well-being of the population as a whole. One of the products sold is the free-range chicken, a product made by many products aside, due to the high costs and low profitability index. Indeed, the objective is to analyze the private and social viability of a small cooperative in the municipality of Horizonte, composed of 88 members, who were benefited by a mechanized free-range chicken slaughterhouse with resources from the São José III Program and incentives from the World Bank. The primary data were collected directly from the farmers, and the secondary data were obtained from the Cooperative of Small and Medium Farmers of Ceará (COOPEMACE), the data referring to the costs of the mechanized slaughterhouse. As methods of analysis, use the private and social analysis of projects through incremental cash flows, adopting two hypotheses: the first, “without project”, comprises the current or conventional production situation without using the slaughterhouse financed by São José III Program for a cooperative; while the second, “with the project”, the breeders started to use the abattoir. Then, the three profitability indicators commonly used to test the project's viability are applied, that is, the benefit-cost ratio (RBC), net present value (NPV), and internal rate of return (IRR). To complement the two assessments, a SWOT analysis was carried out, to highlight the advantages that the cooperative slaughterhouse brings to the cooperative members and highlight the problems encountered with the new project. It appears that both from a private and social point of view, using the cooperative's slaughterhouse for the slaughter of free-range chicken is viable for the members, even if a slaughter fee is R $ 4.00 per chicken, higher than the slaughter traditional price of R $ 2.50. The accepted conclusion is that the slaughterhouse construction project should be carried out, under the indication that this project will bring private, financial, and social gains to the cooperative members, extending to a project involved by the public. Based on the FOFA matrix, it can be concluded that the cooperative members benefit technically and commercially from the installation of the slaughterhouse, while the weaknesses found are mostly easily circumvented, as long as the cooperative's administrative sector is well organized to support the cooperative members.